2017
DOI: 10.1007/s00405-017-4784-4
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of prognostic factors for idiopathic sudden sensorineural hearing loss treated with adjuvant hyperbaric oxygen therapy

Abstract: The objective of this study is to evaluate possible prognostic factors of idiopathic sudden sensorineural hearing loss (ISSNHL) treated with adjuvant hyperbaric oxygen therapy (HBOT) using univariate and multivariate analyses. From January 2008 to October 2016, records of 178 ISSNHL patients treated with auxiliary hyperbaric oxygen therapy were reviewed to assess hearing recovery and evaluate associated prognostic factors (gender, age, localization, initial hearing threshold, presence of tinnitus, vertigo, ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…Xie et al showed that in patients who recovered from hearing loss, HBOT was initiated on average 5.6 days after onset of symptoms, whereas the non-recovered patients were treated on average after 9.1 days ( P = 0.003) [ 120 ].…”
Section: Clinical Use Of Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…Xie et al showed that in patients who recovered from hearing loss, HBOT was initiated on average 5.6 days after onset of symptoms, whereas the non-recovered patients were treated on average after 9.1 days ( P = 0.003) [ 120 ].…”
Section: Clinical Use Of Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…Various prognostic factors have been assessed to predict recovery from SSNHL, including age, onset of hearing loss, initial hearing loss, types of audiogram, accompanying symptoms, therapeutic method, and systemic diseases, such as diabetes mellitus and hypertension. 22,24,43 However, there is no relevant case series research on the prognosis of SSNHL during pregnancy. According to previous studies (Table 1), most pregnant patients with SSNHL achieved complete or partial recovery after treatment according to Siegel's criteria.…”
Section: Prognosismentioning
confidence: 99%
“…The pattern of the audiogram was categorized into four types according to previous studies: ascending, descending, flat, and profound. 2,15…”
Section: Audiologic Evaluation and Recovery Assessmentmentioning
confidence: 99%
“…The initial hearing threshold was a widely debated prognostic factor of SSNHL. 2,15,26,27 Most researchers believed that a higher initial hearing threshold was an indicator of a poor prognosis in SSNHL patient, 2,15,26 but some studies failed to observe an association between initial hearing threshold and hearing improvement. 28 Moreover, Lin et al 21 said that comparisons between those reports must be treated with caution because of different recovery evaluation criteria.…”
Section: Effect Of the Initial Hearing Threshold On Hearing Recoverymentioning
confidence: 99%
See 1 more Smart Citation